Elucidating the Synergistic Behavior of Orientation‐Controlled SnS Nanoplates and Carbon Layers for High‐Performance Lithium‐ and Sodium‐Ion Batteries (Adv. Energy Mater. 8/2022). Issue 8 (24th February 2022) - Lee, Jeongyoub; Choi, Changhoon; Lee, Hyungsoo; Ma, Sunihl; Tan, Jeiwan; Jang, Gyumin; Shim, Sang Gi; Park, Young Sun; Yun, Juwon; Kim, Dong‐Wan; Moon, Jooho
Abstract : Next Generation Batteries In article number 2103138, Dong‐Wan Kim, Jooho Moon and co‐workers present a comprehensive study on the synergistic effect between orientation‐controlled SnS nanoplates and carbon layers for a high‐performance anode in next‐generation batteries. The preferred orientation of the SnS nanoplates along the (111) and (101) planes compared to the (040) planes allows the strong electronic interaction which greatly improves electrical conductivity, ion diffusion, and structural stability, ultimately leading to excellent electrochemical performance.